(untitled) (International Journal of Banking and Finance, 2024)
This study investigated the stock market reaction and the effect of the implementation of Basel II and Basel III on the stock returns of South African banks. In achieving this aim, this study focused on daily and annual data of six commercial banks from 3rd January 2004 to 31st December 2022. The event study methodology was employed to identify abnormal returns around the specified event dates. The effect of the changes in Basel capital requirements on stock returns was not uniform across the four events. The market reacted favourably to the implementation of the Basel II requirements in the country. There was a significantly negative market reaction to the subsequent full implementation of Basel III official. Finally, higher Basel capital requirements (CAR) was associated with lower bank stock returns. The findings implied that bank regulators increase capital to strengthen the banking system but constrain the maximisation of shareholders’ values.